Acotiamide attenuates central urocortin 2‐induced intestinal inflammatory responses, and urocortin 2 treatment reduces TNF‐α productions in LPS‐stimulated macrophage cell lines. Issue 8 (7th February 2020) - Yamawaki, Hiroshi; Futagami, Seiji; Sakasegawa, Noriko; Murakami, Makoto; Agawa, Shuhei; Ikeda, Go; Noda, Hiroto; Kirita, Kumiko; Gudis, Katya; Higuchi, Kazutoshi; Kodaka, Yasuhiro; Ueki, Nobue; et al.
Abstract: Background: To determine whether central and in vitro administration of urocortin 2 (Ucn 2) affected intestinal inflammatory responses in LPS‐stimulated rat models and macrophage cell lines and acotiamide modified mucosal inflammation in this model. Methods: Rats were divided into four groups. LPS‐stimulated group (n = 4); LPS‐ and urocortin 2‐treated group (n = 4); LPS‐ and acotiamide‐treated group (n = 4); and LPS‐, urocortin 2‐, and acotiamide‐treated group (n = 4). CD68‐, CCR2‐, and corticotropin‐releasing hormone receptor type 2 (CRHR2)‐positive cells were assessed by immunostaining. Myeloperoxidase (MPO) activity was measured. TNF‐α, IL‐6, and IL‐4 levels were measured by ELISA method. Gastric emptying and small intestinal transit time were determined using Evans blue. Key Results: Central administration of Ucn 2 significantly aggravated infiltrations of CD68‐ and CCR2‐positive cells in the intestinal mucosa of LPS‐stimulated rat models compared to those in LPS treatment alone. Interestingly, acotiamide treatment significantly reduced the migrations of both CD68‐ and CCR2‐positive cells in the jejunum of central Ucn 2‐treated LPS‐stimulated rat models. Acotiamide significantly reduced the expression levels of IkB‐α phosphorylation in LPS‐ and MCP‐1‐stimulated NR8383 cells. Central administration of Ucn 2 significantly delayed gastric emptying. In contrast, Ucn 2 stimulation significantly reduced TNF‐α and IL‐6 productions in LPS‐stimulated NR8383 cells and astressin B reversed the inhibition of TNF‐α production in stimulated NR8383 cells. Acotiamide (30 μmol/L) significantly reduced TNF‐α and IL‐6 productions in LPS‐ and MCP‐1‐stimulated NR8383 cells. Conclusions and Inferences: Central and in vitro treatments of Ucn 2 affected intestinal inflammatory responses, respectively, and acotiamide improved them. Abstract : Central administration of Ucn 2 significantly aggravated infiltrations of CD68‐ and CCR2‐positive cells in the intestinal mucosa of the LPS‐treated rat models. Acotiamide treatment significantly reduced the migrations of both CD68‐ and CCR2‐positive cells in the jejunum of central LPS‐stimulated Ucn 2‐treated rat models. On the other hand, acotiamide significantly inhibited the expression levels of IkB‐α phosphorylation in LPS and MCP‐1 stimulated NR8383 cells, and reduced both TNF‐α and IL‐6 productions. Central administration of Ucn 2 significantly delayed gastric emptying compared to sham‐operated rat models and accelerated small intestinal transit time in LPS‐stimulated rat models. In vitro Ucn 2 treatment significantly reduced TNF‐α and IL‐6 productions in LPS‐stimulated NR8383 cells.